Contributions of Seweryn Sterling in a fight against tuberculosis and his initiatives in founding healthcare institutions in Lodz - Wysocka-Sendkowska, Natalia (Polish Journal of Public Health, 2012)
Seweryn Sterling, a physician and involved citizen, was an initiator of many healthcare and charity institutions. He was one of the founders of the first anti-tuberculosis ward of Israel and Leona Poznańscy Jewish Hospital in Poland. He also initiated the Anti-tuberculosis League, which played a role of sanatorium of City Hospital. S. Sterling founded the Anna Maria Children Hospital, Ambulance Service, and the charity institution „Kropla Mleka”. That physician was also an author of clinical classification of tuberculosis and an innovative, climatic-hygienic-dietetic method of tuberculosis treatment. He introduced new methods of tuberculosis diagnosis – pulse examination and body temperature measurement.By his struggle with inappropriate hygienic life conditions of Lodz inhabitants, he made their health conditions better. S. Sterling gave speeches on tuberculosis treatment, he published two handbooks: “Suchoty płuc pospolite” and “O leczeniu gruźlicy w szpitalu i w domu”. In his paper “Osobnicza i społeczna walka z gruźlicą” he gave advice to consumptives, while in the paper “Podmiejskie uzdrowiska, szpitale dla chorych piersiowych” he characterized the benefitsof health resorts (sanatoriums). S. Sterling was also an originator of two magazines – “Czasopismo Lekarskie” and “Gruźlica”. He founded a branch of Warsaw Hygienic Association in Lodz as well.